Textile and Trade in Alam Melayu - Swastiwi, Anastasia Wiwik; Simbolon, Gulmok (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Apart from being a trade commodity and cultural driver, textile is always mentioned as something valuable in Alam Melayu. Some Malay manuscripts such as Sullalatus Salatin (Ahmad, 2003), Tawarikh Raja-Raja Melaka dan Pahang, Tuhfat An-nafis (Haji & Ahmad, 1997) and Hikayat Siak, mentioned that the textile acts as the symbol given when facing someone higher, a sign of friendship between kingdoms, proposing to a king's daughter and the cancellation of a king. Textiles in Alam Melayu are found in various types and forms, the function of the textile and its labels. Using the historical method in reconstructing historical events, this article with the theme of social history states that textile and the art of embroidery among Malay women have been fused in people's lives since the past. Relations with the outside world such as China, India, Arabia and Europe, affect various types and forms, functions of textiles and their names.